PENGARUH MEDIA DAN ZAT PENGATUR TUMBUH TERHADAP PERBANYAKAN STEK PUCUK NYAWAI (Ficus variegata Blume) - Danu Danu; Kurniawati P Putri; Dede J Sudrajat (Jurnal Pemuliaan Tanaman Hutan, 2017)
Forest timber plantation of nyawai (Ficus variegate Blume) established by using vegetative propagated seedling from superior individu is very potential to develop for fulfilling the raw material demand of wood processing industries. The purpose of research was to get the optimum rooting medium and growth regulator concentration for rooting shoot cuttings of nyawai. Materials cuttings were provided from seedlings at 12 months age. The experiment was performed as factorial in a completely randomized design with two factors, i.e. rooting media factors (sand, mixed coconut coir dust + rice husk (2: 1, v/v), and mixed coconut coir dust+ husk rice + husk rice charcoal (6: 3: 1, v/v)) and IBA growth regulator concentrations (0, 50, 100,200,400, 600, and 800 mg/l), with three replications so that twenty experimented unit were used at each replication. Rooting percentage, root number, root length, shoot length, root biomass, shoot biomass, and leaf number were evaluated. Based on the result, sand media produced the highest rooted cuttings (88.10%), while the use of IBA showed the trend to increase the number of root with increasing the concentrations, but it influenced to reduce the shoot growth. Combination treatment of sand media and IBA 800mg/l provided the highest rooted cuttings (93.33%) with the number of root 21. Therefore, for the successful propagation of nyawai, cuttings are planted in sand media with IBA 800 mg/l.